Patient‐centered benefit–risk assessment in duchenne muscular dystrophy. Issue 5 (27th January 2017) - Hollin, Ilene L.; Peay, Holly L.; Apkon, Susan D.; Bridges, John F.P.
ABSTRACT: Introduction: This study quantified caregiver and patient preferences for a therapeutic agent with demonstrated pulmonary benefits for Duchenne muscular dystrophy (DMD). Caregiver and patient differences were also explored. Methods: A best–worst scaling survey (BWS) was administered to caregivers and patients. Across 9 profiles, respondents selected the best and worst attributes. Utility scores were estimated using mixed logistic regression. Results: Respondents indicated greatest preference for therapies that maintain their current level of cough strength for 10 years or for 2 years. Preference scores for risks were low: 50% chance of diarrhea and 4 additional blood draws per year. Conclusion: There is a strong preference for pulmonary benefit and willingness to trade off risks and burden to achieve these benefits. In exchange for maintaining cough strength for 10 years, respondents were willing to tolerate high probabilities of diarrhea and additional blood draws. Muscle Nerve 55: 626–634, 2017